Gelar Karya Olahan Kayu Rencek di TK Taruna Cepu - Saputri, Indri (Pena Edukasia, 2023)
The article about "Works of Rencek Wood Processing at Taruna Cepu Kindergarten" is the result of research to understand the existence, variety of products, and the process of making wood crafts. Qualitative research methods are descriptive, that is, to explain a phenomenon. The approach used is a historical/historical approach, while the research location is in Cepu District, Cepu Regency. The purpose of this study is to get an overview of the existence and development of rencek wood crafts in Cepu. The benefit of this research is to provide an overview and contribution to the literature on rencek wood crafts, which is one of the artistic developments that will later be developed towards early childhood edupreneurship learning. The results of this study reveal that rencek wood crafts in the packaging of edupreneurship learning at Cepu Taruna Kindergarten appear to have an impressive history.